2019
DOI: 10.1093/infdis/jiz133
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and Infectious Diseases: A Converging Public Health Crisis

Abstract: A converging public health crisis is emerging because the opioid epidemic is fueling a surge in infectious diseases, such as human immunodeficiency virus infection with or without AIDS, the viral hepatitides, infective endocarditis, and skin and soft-tissue infections. An integrated strategy is needed to tailor preventive and therapeutic approaches toward infectious diseases in people who misuse and/or are addicted to opioids and to concurrently address the underlying predisposing factor for the infections—opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…When it comes to the use of recreational drugs, also referred to as "sexualized drug use," extreme situations may develop in such venues, in particular "chemsex" or swinger settings [66] [67]. That is, using increasing rates of "recreational" party drugs up to opioids when having sex [68] [69] [70] [71]. Such cluster meetings of the vulnerable groups mentioned here have consequences: As the relative compaction of HIV-infected people both with and without cART is higher during these meetings than in situations of casual dates, these cluster arrangements provide a favorable potential for more effective spread of HIV and other STIs.…”
Section: Modern Trendsmentioning
confidence: 99%
“…When it comes to the use of recreational drugs, also referred to as "sexualized drug use," extreme situations may develop in such venues, in particular "chemsex" or swinger settings [66] [67]. That is, using increasing rates of "recreational" party drugs up to opioids when having sex [68] [69] [70] [71]. Such cluster meetings of the vulnerable groups mentioned here have consequences: As the relative compaction of HIV-infected people both with and without cART is higher during these meetings than in situations of casual dates, these cluster arrangements provide a favorable potential for more effective spread of HIV and other STIs.…”
Section: Modern Trendsmentioning
confidence: 99%
“…The augmented use of IDU within the opioid epidemic has led to an increase in viral infections, such as HIV and hepatitis C virus (HCV). HIV and HCV infections are transmitted between individuals through high-risk injection practices, such as sharing syringes, drug paraphernalia, and high dead-space syringes [ 44 ]. Another mode of transmission is unprotected sex, in which one study reported its increase in individuals using non-medical prescription opioids [ 45 ].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…In 2016, injection opioid use was responsible for 13% of new HIV diagnoses and linked to localized outbreaks in Scott County, Indiana and Lawrence and Lowell, Massachusetts [ 44 ]. PWID accounted for 9% (3641/38,739) of new HIV diagnoses in the USA in 2017 [ 46 ].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Emerging literature suggests that certain classes of opioids interact with nonclassical ORs in the CNS, leading to complex physiological regulation (18). In the United States, pharmacological and street opioid use has reached epidemic proportions (19). There are conflicting reports on the net outcome of opioid exposure to the adaptive immune system (5), but the overall profile seems to be immunoinhibitory, limiting inflammation and autoimmunity.…”
Section: Introductionmentioning
confidence: 99%